MATHEMATICAL THINKING RESEARCH BY TURKISH COMMUNITY - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2011)
In this article we give a brief overview of the present state of research conducted by Turkish community on mathematical thinking. Particularly, the goal of this paper is to share some prototypical examples of research conducted in mathematics education by the Turkish mathematics education community, around the theme of mathematical thinking and supporting its development. The research on mathematics education is quite a recent achievement. To review the research on mathematical thinking mathematics educators' studies were researched extensively. Later a series of content analyses of the research publications were conducted to determine the contribution of Turkish researchers on mathematical thinking. Our examination of the selected research studies reveals that the Turkish researcher has contributed rarely to the process aspect of mathematical thinking and extensively to the product of this process and the issues that support or hinder the development of mathematical thinking.
Keywords: PEDAGOGICAL CONTENT KNOWLEDGE; ATTITUDES; EFFICACY; SUBJECT; SKILLS; TOOL